Beneficial rhizosphere bacteria provides active assistance in resisting Aphis gossypiis in Ageratina adenophora - Yu, Youxin; Yang, Zihao; Han, Mengyang; Sun, Shengnan; Xu, Gang; Yang, Guoqing (Frontiers in Plant Science, 2024)
Ageratina adenophora can enhance its invasive ability by using beneficial rhizosphere bacteria. Bacillus cereus is able to promote plant growth and provide a positive feedback effect to A. adenophora. However, the interaction between A. adenophora and B. cereus under the influence of native polyphagous insect feeding is still unclear. In this study, Eupatorium lindleyanum, a local species closely related to A. adenophora, was used as a control, aimed to compare the content of B. cereus in the roots of A. adenophora and rhizosphere soil after different densities of Aphis gossypii feeding, and then investigated the variations in the population of A. gossypii and soil characteristics after the addition of B. cereus. The result showed that B. cereus content in the rhizosphere soil and root of A. adenophora increased significantly under A. gossypii feeding compared with local plants, which also led to the change of -diversity and β-diversity of the bacterial community, as well as the increase in nitrate nitrogen (NO3 --N) content. The addition of B.cereus in the soil could also inhibit the population growth of A. gossypii on A. adenophora and increase the content of ammonium nitrogen (NH4 + -N) in the soil. Our research demonstrated that B. cereus enhances the ability of A. adenophora to resist natural enemy by increasing soil ammonium nitrogen (NH4 + -N) and accumulating other beneficial bacteria, which means that rhizosphere microorganisms help invasive plants defend themselves against local natural enemies by regulating the soil environment.